Analisis Semiotika Charles Morris terhadap Pemaknaan Warna Brave Pink dan Hero Green pada Foto Profil Media Sosial dalam Prahara Agustus 2025 - Aziz, Abdul; Ardiandhini, Aditya Dwi; Puspitasari, Intan; Hutapea, Edison Bonar Tua (SENTRI: Jurnal Riset Ilmiah, 2026)
The phenomenon of using the colors Brave Pink and Hero Green in social media profile pictures during the August 2025 public unrest illustrates how visual symbols influence public perception, emotion, and collective action. Initially non-political, these colors gained new meanings through emotionally charged events and widespread digital participation. This study aims to analyze the semiotic meanings of these colors using Charles Morris' semiotic framework, which includes semantic, syntactic, and pragmatic dimensions. This research employs a qualitative approach with semiotic analysis of visual data (profile images, posters, and social media posts) and supporting online media texts. The findings reveal that Brave Pink symbolizes gentle moral courage rooted in empathy, while Hero Green represents solidarity and moral protection for victims of injustice. The relational use of both colors establishes a collective visual code through which the public express’s identity, ideological stance, and digital solidarity. Pragmatically, these symbols generate social effects such as online participation, spread of peaceful resistance symbols, and reinforcement of networked solidarity. This study demonstrates that color can function as a dynamic social sign, reshaped and negotiated through digital interaction, influencing collective action in contemporary media environments.